Thermal management of discretized heaters using CuW microchannel heat sinks and FC3283 for laser diode applications - Amyx, Isabella Gascon, author; Bandhauer, Todd M., advisor; Dumitrache, Ciprian, committee member; Venayagamoorthy, Subhas Karan, committee member (Colorado State University. Libraries, 2024)
Single-phase cooling using microchannel heat sinks (MCHS) has become a popular approach for overcoming the thermal challenges associated with high-powered microelectronic devices. Thermal management is one of the largest barriers to higher power densities in electronics and frequently limits overall device performance. The implementation of forced convective cooling via single-phase liquid cooling in MCHS reduces the thermal resistance resulting in lower device temperatures at high-power conditions, which can decrease the package size and extend the lifespan of devices. The goal of this effort was to investigate practical cooling solutions for laser diode bars. This study examined the effectiveness of a copper tungsten (CuW) microchannel heat sink paired with a dielectric coolant (FC3283) for dissipating both discrete and uniform heat fluxes up to 600 W/cm2 across a 0.25 cm2 surface area through a numerical and experimental study. CuW was chosen as the MCHS material because it is thermal expansion matched to GaAs, which is a common laser diode substrate. FC3283 serves as a dielectric coolant that is compatible with power electronics cooling. Reasonable agreement was found between the numerical model and the experimental results. The resulting thermal resistance ranged from 0.15 cm2 K/W at the highest flow rate to 0.26 cm2 K/W at the lowest flow rate. The resulting thermal performance from this study proved to be insufficient for maintaining optimal temperatures for laser diode applications. Using the validated model, cooling fluid and geometry modifications proved to have a significant impact on the heat transfer coefficients. This study revealed the importance of considering discrete heat sources separately from uniform heat sources and proved that CuW microchannels can be a promising cooling option toward future advancements of laser diode bars and other high-power microelectronics when using a low viscosity and high thermal conductivity, dielectric cooling fluid and an optimized geometry.